Zebrafish behavioral phenomics employed for characterizing behavioral neurotoxicity caused by silica nanoparticles. (February 2020) - Li, Xiang; Ji, Xiuna; Wang, Rongchun; Zhao, Jinghang; Dang, Jiao; Gao, Yan; Jin, Meng
Abstract: Nowadays, silica nanoparticles (SiNPs) as one of the most productive nano-powder, has been extensively applied in various filed. The potential harm of SiNPs has previously received severe attention. A bulk of researches have proven the adverse effect of SiNPs on the health of ecological organisms and human. However, neurotoxic impacts of SiNPs, still remain in the stage of exploration. The potential neurotoxic effects of SiNPs need to be further explored. And the toxic mechanism needs comprehensive clarification. Herein, the neurotoxicity of SiNPs of various concentrations (100, 300, 1000 μg/mL) on adult zebrafish was determined by behavioral phenotyping and confirmed by molecular biology techniques such as qPCR. Behavioral phenotype revealed observable effects of SiNPs on disturbing light/dark preference, dampening exploratory behavior, inhibiting memory capability. Furthermore, the relationship between neurotoxic symptom and the transcriptional alteration of autophagy- and parkinsonism-related genes was preliminarily assessed. Importantly, further investigations should be carried out to determine the effects of SiNPs to cause neurodegeneration in the brain as well as to decipher the specific neurotoxic mechanisms. In sum, this work comprehensively evaluated the neurotoxic effect of small-sized SiNPs on overall neurobehavioral profiles and indicated the potential for SiNPs to cause Parkinson's disease, which will provide a solid reference for the research on the neurotoxicity of SiNPs. Highlights: Neurobehavioral toxicity of SiNPs was comprehensively determined. SiNPs caused anxiety behavior and suppressed exploratory behavior. SiNPs inhibited memory capability. SiNPs disturbed autophagy- and parkinsonism-related genes expression in the brain.